Esophagogastric junction and esophageal body contraction metrics on high‐resolution manometry predict esophageal acid burden. Issue 5 (21st December 2017) - Rengarajan, A.; Bolkhir, A.; Gor, P.; Wang, D.; Munigala, S.; Gyawali, C. P.
Abstract: Background: Distal contractile integral (DCI) and esophagogastric junction contractile integral (EGJ‐CI) are high‐resolution manometry (HRM) software metrics assessing esophageal motor function in gastroesophageal reflux disease (GERD). Methods: Patients undergoing HRM and ambulatory pH monitoring off antisecretory therapy prospectively completed symptom questionnaires assessing symptom burden and a global symptom score (GSS) at baseline and after GERD therapy. DCI<450 mm Hg/cm/s in ≥5 swallows diagnosed ineffective esophageal motility (IEM); proportions of failed (DCI<100 mm Hg/cm/s) and weak (DCI 100‐450 mm Hg/cm/s) sequences were separately assessed. EGJ‐CI assessed vigor of the EGJ barrier. Univariate and multivariate analyses addressed performance of esophageal body and EGJ metrics in predicting abnormal esophageal reflux burden, and symptom outcome from antireflux therapy. Key Results: Of 188 patients (55.2 ± 0.9 year, 64% F), 42.6% had low EGJ‐CI, and 25.0% had IEM. While low EGJ‐CI was associated with abnormal reflux burden ( P = 0.003), IEM alone was not ( P = 0.2). Increasing proportions of failed swallows predicted abnormal AET better than the current IEM definition. Combined low EGJ‐CI and IEM segregated abnormal total and supine acid burden compared to patients with normal EGJ‐CI and no IEM ( P ≤ 0.007 for each comparison). Medical therapy and surgical antireflux therapy were similarly effective in improving symptom burden; surgery resulted in better outcomes with low EGJ‐CI ( P ≤ 0.04), especially with intact esophageal body motor function ( P = 0.02). Conclusions & Inferences: While abnormal EGJ and esophageal body metrics are collectively associated with elevated esophageal reflux burden, increasing proportions of failed swallows are better predictors of reflux burden and outcome compared to the current IEM definition. Abstract : Software tools are available to interrogate the esophagogastric junction (EGJ) and the esophageal body on high‐resolution manometry (HRM). Upon evaluating 188 patients with pH monitoring off acid suppressive therapy, we demonstrate that a hypotensive EGJ (using the EGJ contractile integral) and ineffective esophageal motility (IEM) collectively are associated with elevated esophageal acid exposure. While isolated low EGJ‐CI was also associated with elevated reflux burden, IEM as currently defined was not. However, increasing proportions of failed sequences were associated with higher acid exposure. A hypotensive EGJ predicted better response to antireflux surgery than medical therapy, especially in the absence of IEM.